A monograph of the Oligochaete family Alluroididae - Jamieson, Barrie G. M.; Fragoso, Carlos (Zootaxa, 2024)
The Alluroididae is a small oligochaete family with 8 genera and 13 known species occurring in freshwaters and in riverine soils in Africa, the Caribbean and Central and South America. It is here argued that their anatomy shows a transition from that of microdriles to that of megadriles (Metagynophora). A detailed description of comparative anatomy is given, followed by the systematics and some aspects of the ecology of all known genera, species and subspecies.